Ultrafine organic aerosol particles inhaled by mice at low doses remain in lungs more than half a year. (29th August 2019) - Parkhomchuk, Ekaterina V.; Prokopyeva, Elena A.; Gulevich, Dayana G.; Taratayko, Anrey I.; Baklanov, Anatoly M.; Kalinkin, Peter N.; Rastigeev, Sergey A.; Kuleshov, Dmitry V.; Sashkina, Kseniya A.; Parkhomchuk, Vasiliy V.
Abstract : Experimental results of the second series of experiments on the penetration of monodisperse polymeric particles, inhaled at low dose by mice, to different organs using direct way of particle registration, based on the ultra‐sensitive accelerator mass spectrometer (AMS), are presented. Polystyrene (PS) beads, composed of radiocarbon‐labeled styrene, were produced for testing them as model organic aerosols. Mice inhaled 14 C‐PS aerosol of 3·10 5 ultrafine particles per 1 cm 3 for 30 minutes every day during 5 days. Long‐term investigation showed that PS ultrafine particles have been effectively accumulated in lungs with the maximum content in the fifth day of postexposure, and have also appeared in liver on the fifth day of exposure and in the brain on the 30th day of experiments. No particles have been detected in kidneys, spleen, and excrements. Thirty‐five millions of particles remained in the lungs after half a year of postexposure showing extremely slow removal of such particles from the organ. Abstract : Ultrafine 14 C‐labeled polystyrene beads were synthesized from 14 C‐methanol, inhaled at low dose by mice, and directly detected in different organs by ultra‐sensitive accelerator mass spectrometer. Thirty‐five millions of particles remained in the lungs after half a year of postexposure.